1998
DOI: 10.3810/pgm.1998.12.389
|View full text |Cite
|
Sign up to set email alerts
|

Trends in smoking-related diseases

Abstract: Although millions of Americans have kicked the habit, the effects of cigarette smoking likely will be around for a long time. What was once regarded as a glamorous habit is now recognized as a health threat and an economic burden. But what headway has been made in the reduction of related morbidity and mortality? The authors of this article review the current epidemiologic data on smoking-related diseases and make an indisputable case for smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Previous studies (8, 10, 18) have demonstrated that smoking is a major risk factor for many respiratory diseases and symptoms with a dose-response relationship. This supports that smoking is an important factor for chronic sputum irrespective of geographical location as well as other smoking-related diseases (10, 19, 20), and that smoking cessation should be encouraged in subjects with chronic sputum to relieve their symptoms.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies (8, 10, 18) have demonstrated that smoking is a major risk factor for many respiratory diseases and symptoms with a dose-response relationship. This supports that smoking is an important factor for chronic sputum irrespective of geographical location as well as other smoking-related diseases (10, 19, 20), and that smoking cessation should be encouraged in subjects with chronic sputum to relieve their symptoms.…”
Section: Discussionsupporting
confidence: 62%
“…Quitting may also have been more difficult for Reservists and National Guard members who faced possible redeployment and ongoing service/stress. Consistent with previous reports, current smoking was related to reduced mental and physical quality of life (Hayes, Dale, Hurt, & Croghan, 1999) and increased report of probable alcohol misuse (Calhoun, Elter, Jones, Kudler, & Straits-Troster, 2008). These findings underscore the continued need to address comorbid mental health and substance use concerns in veterans.…”
Section: Discussionsupporting
confidence: 87%
“…The increase in nicotine self-administration could be a compensatory response to a reduction in nicotine reward after low doses of bupropion. In humans, the majority of studies have demonstrated that bupropion is more effective at improving smoking cessation than placebo [135, 136] . Bupropion has also been reported to reduce nicotine abstinence-associated depression, difficulty concentrating, and irritability, relative to placebo [137] .…”
Section: Ach-based Medication Developmentmentioning
confidence: 99%